Knowledge Engineering and Data Mining - Konys, Agnieszka; Nowak-Brzezińska, Agnieszka (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Knowledge engineering and data mining are fundamental topics in the area of artificial intelligence and knowledge-based systems. This Special Issue covers the entire knowledge engineering pipeline: from data acquisition and data mining to knowledge extraction and exploitation. The reader will find topics including data mining methods, multidimensional data analysis, supervised and unsupervised learning methods, methods of knowledge-based management, language ontologies, ontology learning, and others.